Piperlongumine synergistically enhances the antitumour activity of sorafenib by mediating ROS-AMPK activation and targeting CPSF7 in liver cancer - Liyun Zheng; Shiji Fang; Aifang Chen; Weiqian Chen; Enqi Qiao; Minjiang Chen; Gaofeng Shu; Dengke Zhang; Chunli Kong; Qiaoyou Weng; Suqin Xu; Zhongwei Zhao; et al. (Elsevier, 2022)
Sorafenib, a multikinase inhibitor, is the first-line agent for advanced liver cancer. Sorafenib strongly inhibits both cell proliferation and tumour angiogenesis. However, the development of drug resistance hampers its anticancer efficacy. To improve the antitumour activity of sorafenib, we demonstrate that piperlongumine (PL), an alkaloid isolated from the fruits and roots of Piper longum L., enhances the cytotoxicity of sorafenib in HCCLM3 and SMMC7721 cells using the cell counting kit-8 test. Flow cytometry analysis indicated that PL and sorafenib cotreatment induced robust reactive oxygen species (ROS) generation and mitochondrial dysfunction, thereby increasing the number of apoptotic cells and the ratio of G2/M phase cells in both HCCLM3 and SMMC7721 cells. Furthermore, AMP-protein kinase (AMPK) signalling was activated by excess ROS accumulation and mediated growth inhibition in response to PL and sorafenib cotreatment. RNA-sequencing analysis indicated that PL treatment disrupted RNA processing in HCCLM3 cells. In particular, PL treatment decreased the expression of cleavage and polyadenylation specificity factor 7 (CPSF7), a subunit of cleavage factor I, in a time- and concentration-dependent manner in HCCLM3 and SMMC7721 cells. CPSF7 knockdown using a gene interference strategy promoted growth inhibition of PL or sorafenib monotherapy, whereas CPSF7 overexpression alleviated the cytotoxicity of sorafenib in cultured liver cancer cells. Finally, PL and sorafenib coadministration significantly reduced the weight and volume of HCCLM3 cell xenografts in vivo. Taken together, our data indicate that PL displays potential synergistic antitumour activity in combination with sorafenib in liver cancer.